Facing the challenge of multidrug‐resistant gram‐negative bacilli in Australia. Issue 5 (16th March 2015) - Harris, Patrick; Paterson, David; Rogers, Benjamin
Summary: Multidrug‐resistant (MDR) gram‐negative bacilli (GNB) are now globally widespread and present a major challenge to modern medical practice. Resistance to common antibiotics such as ceftriaxone is becoming more frequent in Australia, primarily mediated by extended‐spectrum β‐lactamase enzymes in common organisms such as E scherichia coli, and may occur in both hospital‐ and community‐acquired infections. Carbapenem‐resistant Enterobacteriaceae have emerged rapidly in recent years and are well established in many countries in the Asia–Pacific region. Although rare at present in Australia, they have caused significant nosocomial outbreaks. GNB have numerous mechanisms by which they can develop antibiotic resistance. Genes that encode extended‐spectrum β‐lactamases or carbapenemases are frequently co‐located with multiple other resistance determinants on highly transmissible genetic structures such as plasmids. A key risk factor for infection with MDR GNB is travel to countries with high rates of resistance, especially with health care exposure. With limited prospects for new antibiotics in late‐stage development that are active against MDR GNB, our national response to these challenges will require a multifaceted approach, including widespread implementation of antimicrobial stewardship, enhanced surveillance, targeted screening of at‐risk patients and improved infection control practices. In the longer term, restriction of agricultural use of antibiotic classes critical to human medicine, removal of barriers to new drug development, and technological advances in rapid microbiological diagnostics will be required.